Superficial circumflex iliac perforator flaps for maxilla defects with intraoral anastomosis or pedicle elongation techniques - Wei Wang; Xiao-Ming Lyu; Yi-Wei Zhong; Yan Shi; Jie Zhang; Raymond Chung Wen Wong; Lei Zheng (BMC, 2024)
Abstract Background To evaluate the feasibility and safety of the superficial circumflex iliac perforator flap (SCIP) for maxillary reconstruction with intraoral anastomosis, pedicle elongation, and super-microsurgery techniques to overcome its anatomical shortcomings due to the attractive merits of the flap. Methods Patients who underwent reconstruction of maxillary defects with SCIPs from July 2020 to December 2022 were included. Intraoral anastomosis, pedicle elongation, and super-microsurgery were performed during surgery with or without a neck incision. The sizes, pedicle lengths, inner calibres of vessels, complications and flap survival statuses were recorded. Results A total of 12 patients were included, with 3 males and 9 females, and the median age was 45 years, ranging from 14 to 74 years. There were 5 class IIa and 7 class IIb defects, 6 cases underwent maxillary defect reconstruction via SCIPs with intraoral anastomosis, and the other 6 cases with distally design and/or de-epidermis pedicle elongation. Super-microsurgery interventions were needed in 5 patients. The size ranged from 3 cm×4 cm to 6 cm×8 cm. The pedicle length ranged from 4 cm to 12 cm, with a median of 6 cm. The inner caliber of the arteries ranged from 0.7 mm to 2 mm, with a median of 1 mm, and the veins ranged from 1.5 mm to 4 mm, with a median of 2.5 mm. All the flaps survived, and no donor site complications occurred. Conclusion Superficial circumflex iliac perforator flaps can be regarded as feasible and safe choices for maxillary defects with the support of intraoral anastomosis, pedicle elongation and super-microsurgery.